IFN-γ synergism with poly I:C reduces growth of murine and human cancer cells with simultaneous changes in cell cycle and immune checkpoint proteins. (1st December 2018) - Guinn, Zachary P.; Petro, Thomas M.
Abstract: Previously, we reported that IFN-γ and poly I:C, a TLR3 Pattern Recognition Receptor (PRR) agonist, reduces growth of and induces Cleaved-Caspase-3, ISG54 and p27Kip in B16 melanoma cells. Here, analysis of IFN-γ/PRR synergism was expanded with UM-SCC1 and UM-SCC38 human squamous carcinoma cells and other PRR agonists. As in B16 cells, poly I:C plus IFN-γ synergism reduced UM-SCC1 and UM-SCC38 growth, and no more than 24 h was needed for significant growth reduction. IFN-γ synergism to stem B16 growth also occurred with TLR7, TLR9, TLR4, and STING agonists, but not TLR2 agonist. IFN-γ synergized with TLR3 and TLR4 agonists reducing UM-SCC1 growth, and with TLR7 and TLR3 agonists reducing UM-SCC38 growth. IFN-γ plus poly I:C, which had the most pronounced effect, decreased cyclin-D1, increased G1 cell cycle arrest, and increased Cleaved caspase-3 in B16 cells, as well as RAW264.7, a virus-transformed murine macrophage cell line. Finally, IFN-γ plus poly I:C modulated total but not cell surface expression of immune checkpoint protein PD-L1, as well as cell cycle checkpoint proteins in B16 cells. Thus IFN-γ plus poly I:C, and other PRR agonists, may well be effective adjuvants to cancer immunotherapy against several tumor cell types. Highlights: Interferon-gamma with poly I:C arrest human and mouse tumor cell growth. Interferon-gamma with poly I:C decrease expression of Cyclin-D1 and modulate PD-L1. IRF-3 is pivotal to decreased expression of Cyclin-D1 by Interferon-gamma plus poly I:C. Loxoribine, a TLR7 agonist, alone greatly reduces human and mouse tumor cell growth.